Sistem Remunerasi terhadap Motivasi Kerja dan Kinerja Perawat - Monita Fenny Sudarsono; Hadi Masyurrosyidi; Djazuly Chalidyanto (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of the remuneration system on nurses' work motivation and nurse performance in East Java Private Hospitals. The research method used is an observational method with a cross-sectional design. The result of this research is that the remuneration system on motivation shows a significance value of 0.022 (a = 0.05). The reason for performance offers a significance value of 0.001 (a=0.05). Meanwhile, the remuneration system has no significant effect on performance, with a significance value of 0.487. In conclusion, the remuneration system has a significant influence on motivation. Motivation has a significant impact on the performance of nurses in East Java Private Hospitals so that the remuneration system can affect motivation. Keywords: Performance, Motivation, Nurse, Remuneration System